Legalitas Literasi Financial Techology: Peer to Peer Lending Berdasarkan Perspektif Hukum Ekonomi Syari’ah - Sayyidah Sekar Dewi Kulsum; Muhamad Bisri Mustofa; Siti Wuryan; A.Khumaidi Ja’Far; Siti Mahmudah (Adzkiya : Jurnal Hukum dan Ekonomi Syariah, 2022)
Objectives of this study were to determine an implementation of Information technology-based borrowing and lending service and legality with application of interest in the term of Sharia Economic law perspectives. The method that using was qualitative methods. It by processed secondary data that consisted of theoretical study of P2P lending that analyzing based on Maqāṣid Asy-Syarĭ'ah theoretical framework. Based on the findings, an information technology-based borrowing and lending service in Indonesia had several weaknesses. They were absence of maximum loan interest rate determinations, dispute resolution provisions, sanctions to the platform that weren’t registeringby OJK, and socialization regarding service regulations that have not been maximized. According to Sharia Economic Law, this transaction is classified as debts (Al - Qarḍ). The process of Bonding and applying flowers in it is filled with elements of Maysĭr, Garār, and Ribā. So that could be asserted that a legality of P2P lending with an application of interested from Islamic law perspective was aram.